(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
To achieve success in teaching, the teacher must have the necessary information and knowledge from the new educational theories and educational psychology. The purpose of this paper is to show how a teacher who has more psychological knowledge is more successful than other instructors.